Recent Progress in Saliva-Based Sensors for Continuous Monitoring of Heavy Metal Levels Linked with Diabetes and Obesity - Liliana Anchidin-Norocel; Wesley K. Savage; Alexandru Nemțoi; Mihai Dimian; Claudiu Cobuz (Chemosensors)
Sensors are versatile technologies that provide rapid and efficient diagnostic results, making them invaluable tools in public health for measuring and monitoring community exposure to environmental contaminants. Heavy metals such as lead, mercury, and cadmium, commonly found in food and water, can accumulate in the body and have toxic effects, contributing to the development of conditions like obesity and diabetes. Traditional methods for detecting these metals often require invasive blood samples; however, sensors can utilize saliva, offering a noninvasive and simplified approach for public health screening. The use of saliva as a diagnostic fluid represents a major advance in population health monitoring due to its low cost, noninvasiveness, and ease of collection. Recent advances in sensor technology have enabled the development of diagnostic tests that link heavy metal levels in saliva with the risk of developing obesity and diabetes. Optimizing these sensors could facilitate the identification of individuals or groups at risk, enabling targeted, personalized preventive measures. Sensors that use saliva for detecting heavy metals hold promise for diagnosing and preventing metabolic diseases, providing valuable insights into the link between heavy metal exposure and metabolic health.